2019
DOI: 10.1007/s00421-019-04266-8
|View full text |Cite
|
Sign up to set email alerts
|

Exercise tolerance during flat over-ground intermittent running: modelling the expenditure and reconstitution kinetics of work done above critical power

Abstract: Purpose We compared a new locomotor-specific model to track the expenditure and reconstitution of work done above critical power (W´) and balance of W´ (W´BAL) by modelling flat over-ground power during exhaustive intermittent running. Method Nine male participants completed a ramp test, 3-min all-out test and the 30–15 intermittent fitness test (30–15 IFT), and performed a severe-intensity constant work-rate trial (SCWR) at the maximum oxygen uptake velocity (vV̇O2max). Four intermittent trials followed: 60-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
0
10
1
Order By: Relevance
“…However, typical power meters 19 provide P ext or P tot but not P int , which makes the estimation of CP ext or CP tot essential to perform training based on power-based intensity domains. Besides, Vassallo et al 34 recently estimated a running CP tot from a 3-minute all-out test performed on an outdoor athletic track. The authors obtained a CP tot of 6.64 W/kg (assuming a body mass of 68 kg), which is 15% smaller than the one reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, typical power meters 19 provide P ext or P tot but not P int , which makes the estimation of CP ext or CP tot essential to perform training based on power-based intensity domains. Besides, Vassallo et al 34 recently estimated a running CP tot from a 3-minute all-out test performed on an outdoor athletic track. The authors obtained a CP tot of 6.64 W/kg (assuming a body mass of 68 kg), which is 15% smaller than the one reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The present study observed that τD′ was not related to CS regardless of linear or nonlinear equations used. On the other hand, τW′ was previously related to D CP or CP in cycling, running, and handgrip exercises ( Skiba et al, 2012 ; Broxterman et al, 2016 ; Vassallo et al, 2020 ). As previously mentioned, it is possible that no relationship was found because of the high within-subject variability of τD'.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, it is possible that no relationship was found because of the high within-subject variability of τD'. Also, the discrepancies between results might, to a large extent, be due to these studies employing recovery intensity based on different exercise domains ( Skiba et al, 2012 ; Vassallo et al, 2020 ) or different contraction–relaxation cycles ( Broxterman et al, 2016 ). In accordance, when performing a visual inspection in figures presented by Skiba et al (2012) , Vassallo et al (2020) , and Broxterman et al (2016) , the relationships would likely have a worse or no fit if only one exercise domain were used for recovery intensity ( Skiba et al, 2012 ; Vassallo et al, 2020 ) or contraction–relaxation cycle ( Broxterman et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, when applied to velocity, work performed below the critical velocity threshold is measured in m·s −1 , and the finite work capacity is measured in meters (64). It has previously been suggested that parameters derived from this power/velocity-time relationship can be used to describe a “gold standard” demarcation of the metabolic steady state and the finite work capacity of individuals (64,66).…”
Section: Metabolic Power Thresholdsmentioning
confidence: 99%